KONTRIBUSI LATIHAN PNF DAN LATIHAN SHUTTLE RUN TERHADAP KEMAMPUAN TENDANGAN DOLLYO CHAGI PADA ATLET PRA-JUNIOR PUTRA USIA 10-13 TAHUN TIGER TAEKWONDO CLUB BINJAI TAHUN 2021 - Nisrina Naila; Imran Akhmad (Journal Physical Health Recreation (JPHR), 2021)
This study aims to determine the contribution of PNF training and Shuttle Run training to Dollyo Chagi's kicking ability in male Pre-Junior athletes aged 10-13 years Tiger Sumatra Taekwondo Club Binjai 2021. The method used in this study is an experimental method with data collection techniques involving two independent variables, namely PNF and Shuttle Run on the dependent variable dollyo chagi kick ability. The population in this study amounted to 30 athletes, and the sample in this study amounted to 10 athletes who were selected by purposive sampling method. The design of this study used a post-test one group design. The results of this study indicate that (1) There is There is a contribution of PNF training to the dollyo chagi kick ability of 79% (2) There is a contribution of Shuttle Run training to the dollyo chagi kick ability 19.2%, (3) There is a contribution of PNF and Shuttle Run training to the dollyo chagi kicking ability known by looking at the value of R (r2 x 100%). The value of r2 is 0.911, so it is known that the amount of contribution is 91.1%.